A RETROSPECTIVE COHORT STUDY OF LONG-TERM MONITORING OF ADULT PATIENTS WITH NON-SEVERE RHEUMATIC MITRAL STENOSIS, DELHI, INDIA: INSIGHTS INTO DISEASE PROGRESSION. - Singh, Anil Kumar; Singh, Payal (Student’s Journal of Health Research Africa, 2024)
Background Long-term monitoring of adult patients with non-severe rheumatic mitral stenosis is crucial for understanding disease progression and optimizing patient care. The study aimed to assess the long-term outcomes and progression patterns of adult patients diagnosed with non-severe rheumatic mitral stenosis, providing insights into the natural history of the disease and guiding clinical management strategies. Methods The retrospective cohort study involved 118 adult patients over a period spanning from 2022 to 2023. Participants were assessed for demographic characteristics, clinical conditions, lifestyle factors, and echocardiographic parameters. Patients were distributed into two groups based on disease progression status: indolent disease (n=78) and progressive disease (n=40). Statistical analyses were performed to calculate differences between groups and identify predictors of disease progression and clinical complications. Results The study cohort had an average age of 52 years, with a balanced gender distribution. Clinical evaluation revealed that dyspnea on exertion was the most common symptom, and comorbidities such as hypertension and diabetes mellitus were prevalent. Initial echocardiographic assessment showed preserved left ventricular function, with a mean mitral valve area of 1.8 cm² and a mean gradient over the mitral valve of 6 mmHg. During follow-up, 66% of patients exhibited an indolent disease course, while 34% demonstrated progressive disease. Conclusion Regular echocardiographic evaluation, combined with appropriate medical management, is essential for optimizing results in patients with non-severe rheumatic mitral stenosis. Early detection of disease progression and timely intervention are crucial in mitigating long-term adverse outcomes. Recommendations Healthcare providers should emphasize the importance of regular follow-up and adherence to medical therapy in individuals with non-severe rheumatic mitral stenosis. Furthermore, efforts should be made to address modifiable risk factors like hypertension and diabetes mellitus to prevent disease progression and reduce the risk of clinical complications.